KEPEMIMPINAN WALI NAGARI SE-KECAMATAN KOTO PARIK GADANG DIATEH KABUPATEN SOLOK SELATAN - YOFI ELFAMEDRA (Universitas Negeri Padang, 2018)
This article describe result of research about leadership Guardian Village in the Koto Parik Gadang Diateh Districts in Solok Southern District. The population of this research are 69 employee and 59 employee were taken as a sample. Sampling technics were using is Simple Random Sampling with Krejchi Table. The instrument used in this research is questionnaire and analyzed by average. In general, the result of this research is leadership Guardian Village in the Koto Parik Gadang Diateh Districts in Solok Southern District have is good enough at 3,45.